2006
DOI: 10.1007/s11119-006-9012-y
|View full text |Cite
|
Sign up to set email alerts
|

An economic evaluation of site-specific herbicide application

Abstract: The objective of this study was to determine if site-specific application of postemergence herbicide was economically viable with current technologies. This objective was accomplished by: developing an algorithm that determined the economic optimal postemergence herbicide rate; creating models to determine the impact that postemergence herbicide rate has on yield; and determining whether site-specific application of postemergence herbicide has greater net returns than those from a uniform application of postem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 7 publications
(11 reference statements)
0
16
0
3
Order By: Relevance
“…Thanks to the zone-to-zone input rationalization and treatment, precision technology may ensure more efficient production with a lower environmental impact [15][16][17][18][19][20]. Accuracy is necessary during the correct application of precision technology, but often, this becomes a factor that obstructs its use on farms [21].…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to the zone-to-zone input rationalization and treatment, precision technology may ensure more efficient production with a lower environmental impact [15][16][17][18][19][20]. Accuracy is necessary during the correct application of precision technology, but often, this becomes a factor that obstructs its use on farms [21].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the literature examining the penetration of the elements of precision plant production (Jacobsen et al, 2011;McBride and Daberkow, 2003), the proportions of farms converting to precision farming were set at 15, 25, and 40 per cent using pessimistic, neutral and optimistic scenarios, respectively. The expected savings in pesticide use, 25, 35 and 50 per cent were determined from the literature (Batte and van Buren, 1999;Pecze, 2006;Rider et al, 2006;Chavas, 2008). …”
Section: Methodology Estimation Of Savings In Pesticide Applicationsmentioning
confidence: 99%
“…Precision farming could result in less agrochemical being distributed in the environment, and it also could be one of the basic pillars of effi cient agriculture while large-scale production structure, investments, organisational structures and operational mechanisms remain. Earlier studies estimated 20-60 per cent pesticide savings owing to precision plant protection and 0-30 per cent savings in fertiliser use depending on the yield homogeneity (Lowenberg-DeBoer and Swinton, 1997;Batte and van Buren, 1999;Pecze, 2006;Rider et al, 2006). Also, for the producer this method of farming can be a tool for reducing the risks associated with production.…”
Section: Introductionmentioning
confidence: 99%
“…Towards these lines, Bongiovanni and Lowenberg-Deboer [5] showed that, even by cutting N rate to half of the recommended uniform rate, farm profitability is not compromised. Some other studies estimated savings of 20-60% in pesticide use, and up to 30% in fertilizer application depending on yield homogeneity [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%